A metodologia de multicritério como ferramenta para a tomada de decisões gerenciais: um estudo de caso - Freitas, André Luís Policani; Marins, Cristiano Souza; Souza, Daniela de Oliveira (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper presents a supportive model to the decision-making process towards the analysis of the bestcandidate for the position of Production Manager. The ability to analyze situations which comprehendsimultaneously qualitative and quantitative criteria from the decision-making process, such as the personalcharacteristics, education and professional experience etc., is highlighted as an important characteristic of themodel. The analytic method embedded in the decision-making process model was the AHP (Analytic HierarchyProcess), due to its flexibility when applied to problems related to the decision-making process. The method ofthis model was operationalized through the Expert Choice software, which guarantees the quality in thedevelopment of the model and stimulates the participation of several members of the organization.Keywords: Multicriteria; AHP; Experiment.